Efficacy of Turkey berry (Solanum torvum) for in vitro management of rice blast pathogen, Pyricularia oryzae / Siti Nurarysha Azman - Azman, Siti Nurarysha (Faculty of Plantation and Agrotechnology, 2018)
Rice blast diseases have become major nuisance of paddy production nowadays. Rice blast is one of the most destructive paddy diseases worldwide. Rice blast, caused by the fungus Pyricularia oryzae which have infected many paddy fields in Malaysia and other regions that grow paddy in the world. Application of chemical fungicides usually significance in controlling the disease only for short term period . For long term period, application of chemicals will cause a major impacts to other living organisms and environment. Thus, it is very important to search for other alternatives that will not bring harm to the environment. This study was conducted to evaluate the effectiveness of crude extract of Solanum torvum to control rice blast. The parameters of this study were Pyricularia oryzae (Pathogen of rice blast) and Solanum torvum’s crude extract. The methodology used in this study was in vitro control of rice blast pathogen, Pyricularia oryzae by conducting poisoned food technique. Pure culture of Pyricularia oryzae was sub cultured on Potato Dextrose Agar (PDA). The sub cultured pathogen were transferred on the crude extract of Solanum torvum and after 5 days, the diameter of Pyricularia oryzae grown on crude extract can be measured. From this study, the results obtained show that both leaf and fruit extract of Solanum torvum is effective in controlling rice blast. This can be proven by comparing the diameter of Pyricularia oryzae grown on PDA amended with fruit and leaf extract with the negative control.